PENGARUH PENGGUNAAN MODEL PBL TERHADAP KETERAMPILAN MENULIS TEKS EKSPOSISI SISWA KELAS VII SMP NEGERI 31 PADANG - Oksalia, Ilma; Gani, Erizal; Tamsin, Andria Catri (Universitas Negeri Padang, 2016)
ABSTRACT This is article of research is to description the effects of the using the model of problem based learning towards the skills of writing a text eksposition of the seventh grade students at SMP Negeri 31 Padang. The method used is this research is quasy experiment method. Based on the results of data analysis it was concluded the following three points. First, the skills of writing a text exposition of students of class VII SMP Negeri 31 Padang without using model of problem based learningis located on qualifications is enough (62,38). Second, the skills of writing a text exposition of students of class VII SMP Negeri 31 Padang using model of problem based learning is located on qualifications is good (78,25). Third, based on the result of test-t, there is effects of model of problem based learning towards the skills of writing a text exposition of students of class VII SMP Negeri 31 Padang because taritmatic> t table.Â Kata kunci : effects, model PBL, text eksposition